Capacity of soil loss control in the Loess Plateau based on soil erosion control degree - Gao, Haidong; Li, Zhanbin; Jia, Lianlian; Li, Peng; Xu, Guoce; Ren, Zongping; Pang, Guowei; Zhao, Binhua (Journal of geographical sciences, 2016)
The capacity of soil and water conservation measures, defined as the maximum quantity of suitable soil and water conservation measures contained in a region, were deter- mined for the Loess Plateau based on zones suitable for establishing terraced fields, forest- land and grassland with the support of geographic information system （GIS） software. The minimum possible soil erosion modulus and actual soil erosion modulus in 2010 were calcu- lated using the revised universal soil loss equation （RUSLE）, and the ratio of the minimum possible soil erosion modulus under the capacity of soil and water conservation measures to the actual soil erosion modulus was defined as the soil erosion control degree. The control potential of soil erosion and water loss in the Loess Plateau was studied using this concept. Results showed that the actual soil erosion modulus was 3355 t-km-2.a-1, the minimum pos- sible soil erosion modulus was 1921 t.km-2.a-1, and the soil erosion control degree was 0.57 （medium level） in the Loess Plateau in 2010. In terms of zoning, the control degree was rela- tively high in the river valley-plain area, soil-rocky mountainous area, and windy-sandy area, but relatively low in the soil-rocky hilly-forested area, hilly-gully area and plateau-gully area. The rate of erosion areas with a soil erosion modulus of less than 1000 t.km-2.a-1 increased from 50.48% to 57.71%, forest and grass coverage rose from 56.74% to 69.15%, rate of ter- raced fields increased from 4.36% to 19.03%, and per capita grain available rose from 418 kg.a-1 to 459 kg.a-1 under the capacity of soil and water conservation measures compared with actual conditions. These research results are of some guiding significance for soil and water loss control in the Loess Plateau.